Analysis of born globals internationalisation strategy and partnerships. (25th September 2019) - Dourado, André Luís Figueiredo Santana; Figueira, Mariane; Castro, Cleber Carvalho De
The specific objectives of this study include characterising the born globals founders' profile, identifying the factors that lead the companies to globalise, identifying the reasons of choosing to enter certain countries, verifying how the internationalisation strategic behaviour of born globals had been modified through the years, as well as verifying the role that partnerships represented to born globals. Three organisations from Brazil and Italy were analysed. Interviews were carried out with the organisations' stakeholders through a semi-structured questionnaire previously elaborated. All the interviews were recorded and then transcribed and submitted to content analysis. The study helped clarify some topics related to the role played by partnerships and the founders' profile, more specifically, the temporal aspect of partnerships and the necessary entrepreneur profile of founders. Finally, the study has also found that some concepts in the literature of born globals are not in agreement with the results from the sample analysed.